2014
DOI: 10.1177/1077699014554766
|View full text |Cite
|
Sign up to set email alerts
|

News Consumers, Opinion Leaders, and Citizen Consumers

Abstract: The intersection of consumer culture and civic life has long been a topic of academic discussion. This study revisits the relationship between consumption and civic engagement and investigates the moderators of this relationship. Specifically, we focus on news consumption and opinion leadership as intervening factors that condition the way consumption and civic life are interconnected. Our data reveal that both socially conscious consumption and status-oriented consumption are positively related with civic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 34 publications
1
0
0
Order By: Relevance
“…Many studies have concluded that citizens take advantage of these online opportunities to get involved in public affairs (Bakker & de Vreese, 2011;Cho, Keum, & Shah, 2015;Hargittai & Shaw, 2013;Lee, 2015). This is consistent with studies that find consumption of traditional news media, such as newspapers, to be positively related with civic engagement and political participation (Peer, Malthouse, & Calder, 2003;Rothenbuhler et al, 1996;Shaker, 2014).…”
Section: The Rise Of the Online Communitysupporting
confidence: 64%
“…Many studies have concluded that citizens take advantage of these online opportunities to get involved in public affairs (Bakker & de Vreese, 2011;Cho, Keum, & Shah, 2015;Hargittai & Shaw, 2013;Lee, 2015). This is consistent with studies that find consumption of traditional news media, such as newspapers, to be positively related with civic engagement and political participation (Peer, Malthouse, & Calder, 2003;Rothenbuhler et al, 1996;Shaker, 2014).…”
Section: The Rise Of the Online Communitysupporting
confidence: 64%
“…In the literature, several studies underline how sustainable and 'environmentally friendly' products have a strong impact on product evaluation, trust and purchasing decisions [42][43][44][45][46][47][48]. However, as most consumers do not have the technical skills or other resources to discriminate independent attributes of the quality of the fish caught, such as location or method of fishing, consumers currently struggle to recognize these attributes not always easily identifiable at the time of purchase and above all rely on the seller's trust and price [49].…”
Section: Consumers' Attitude Towards Fresh Fish Productsmentioning
confidence: 99%
“…News today plays an important role in shaping consumers' opinions. The news media has a profound influence on the way consumers obtain and process information (Cho, Keum, and Shah, 2015). Additionally, news helps frame information that can potentially lead consumers to a biased or selective viewpoint (Lecheler, Bos, and Vilengenthart, 2015).…”
Section: Introductionmentioning
confidence: 99%